Single-Molecule Tracking dataset for histone H3 (hht1) from live and fixed cells of Schizosaccharomyces pombe - Akriti Kumari; Nitesh Kumar Podh; Sucharita Sen; Kirti Kashyap; Sahil Islam; Anupam Gupta; Eerappa Rajakumara; Mridula Nambiar; Gunjan Mehta (Scientific Data)
Abstract Single-molecule tracking provides direct real-time measurements of protein dynamics in live cells with high spatiotemporal resolution. In the last decade, this method has been adopted by several labs to understand the dynamics of DNA replication, transcription, telomerase, chromatin remodeling, etc. in a variety of model systems (bacteria, yeast S. cerevisiae, cell lines, embryo). However, it has not been employed for the yeast Schizosaccharomyces pombe, despite being a valuable model system. Here, we present single-molecule tracking datasets for chromatin-bound histone H3 (Hht1) in live and fixed cells and freely diffusing GFP in S. pombe nuclei to benchmark the diffusion parameters (diffusion coefficient, mean squared displacement, fraction of bound molecules, residence time). These parameters will be used to differentiate chromatin-bound molecules from unbound (free) molecules of any protein. It will be a valuable resource for any lab that starts employing this method for studying protein dynamics. This dataset can also be used to validate the performance of various tracking software and as a training dataset for machine learning-based automated tracking.